Exciton fine structure inInGaAs∕GaAsquantum dots revisited by pump-probe Faraday rotation - Yugova, I. A.; Greilich, A.; Zhukov, E. A.; Yakovlev, D. R.; Bayer, M.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Robust manipulation of electron spin coherence in an ensemble of singly charged quantum dots - Greilich, A.; Wiemann, M.; Hernandez, F. G. G.; Yakovlev, D. R.; Yugova, I. A.; Bayer, M.; Shabaev, A.; Efros, Al. L.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Universal behavior of the electrongfactor inGaAs∕AlxGa1−xAsquantum wells - Yugova, I. A.; Greilich, A.; Yakovlev, D. R.; Kiselev, A. A.; Bayer, M.; Petrov, V. V.; Dolgikh, Yu. K.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Experimental imaging and atomistic modeling of electron and hole quasiparticle wave functions inInAs∕GaAsquantum dots - Bester, G.; Reuter, Dirk; He, Lixin; Zunger, A.; Kailuweit, P.; Wieck, A. D.; Zeitler, U.; Maan, J. C.; Wibbelhoff, O.; Lorke, A. (Physical Review B)

Measurement of the specific heat of a fractional quantum Hall system - Schulze-Wischeler, F.; Zeitler, U.; v. Zobeltitz, C.; Hohls, F.; Reuter, Dirk; Wieck, A. D.; Frahm, H.; Haug, R. J. (Physical Review B)

Systematic study of carrier correlations in the electron-hole recombination dynamics of quantum dots - Berstermann, T.; Auer, T.; Kurtze, H.; Schwab, M.; Yakovlev, D. R.; Bayer, M.; Wiersig, J.; Gies, C.; Jahnke, F.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Hole levels in InAs self-assembled quantum dots - Blokland, J. H.; Wijnen, F. J. P.; Christianen, P. C. M.; Zeitler, U.; Maan, J. C.; Kailuweit, P.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Ethanol adsorbed on ice: A first-principles study - Thierfelder, C.; Schmidt, Wolf Gero (Physical Review B)

Transport properties of magnetic tunnel junctions withCo2MnSielectrodes: The influence of temperature-dependent interface magnetization and electronic band structure - Schmalhorst, J.; Thomas, A.; Kämmerer, S.; Schebaum, O.; Ebke, D.; Sacher, Marc; Reiss, G.; Hütten, A.; Turchanin, A.; Gölzhäuser, A.; Arenholz, E. (Physical Review B)
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Metallodielectric photonic crystal superlattices: Influence of periodic defects on transmission properties - Zentgraf, Thomas; Christ, A.; Kuhl, J.; Gippius, N. A.; Tikhodeev, S. G.; Nau, D.; Giessen, H. (Physical Review B)

Controlling the interaction between localized and delocalized surface plasmon modes: Experiment and numerical calculations - Christ, A.; Zentgraf, Thomas; Tikhodeev, S. G.; Gippius, N. A.; Kuhl, J.; Giessen, H. (Physical Review B)

Role of quantum capacitance in coupled low-dimensional electron systems - Ruß, M.; Meier, C.; Lorke, A.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Experimental evidence of the ideal de Haas–van Alphen effect in a two-dimensional system - Wilde, M. A.; Schwarz, M. P.; Heyn, Ch.; Heitmann, D.; Grundler, D.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Tailored quantum dots for entangled photon pair creation - Greilich, A.; Schwab, M.; Berstermann, T.; Auer, T.; Oulton, R.; Yakovlev, D. R.; Bayer, M.; Stavarache, V.; Reuter, Dirk; Wieck, A. (Physical Review B)

Theory of ultrafast nonlinear optics of Coulomb-coupled semiconductor quantum dots: Rabi oscillations and pump-probe spectra - Danckwerts, J.; Ahn, K. J.; Förstner, Jens; Knorr, A. (Physical Review B)
We investigate the optical properties of a Coulomb-coupled double-quantum dot system excited by coherent light pulses. Basic effects of Coulomb coupling regarding linear and nonlinear optical processes are discussed. By numerically solving the Heisenberg equation of motion we are able to present the temporal evolution of the system’s density matrix for a wide range of coupling parameters. The two main coupling effects in dipole approximation, biexcitonic shift and Förster energy transfer, are investigated and their qualitative and quantitative influence on absorption spectra, Rabi oscillations, and single- and two-pulse excitation is discussed. We present simulated differential transmission spectra to allow for comparison with recent experimental studies.
Keywords: tet_topic_qd

Tight-binding model for semiconductor quantum dots with a wurtzite crystal structure: From one-particle properties to Coulomb correlations and optical spectra - Schulz, S.; Schumacher, Stefan; Czycholl, G. (Physical Review B)

Experimental and theoretical evidence for a hydrogen stabilizedc(2×2)reconstruction of the P-rich InP(001) surface - Letzig, T.; Willig, F.; Hahn, P. H.; Schmidt, Wolf Gero (Physical Review B)

Clean and pyrrole-functionalized Si- and C-terminated SiC surfaces: First-principles calculations of geometry and energetics compared with LEED and XPS - Preuss, M.; Bechstedt, F.; Schmidt, Wolf Gero; Sochos, J.; Schröter, B.; Richter, W. (Physical Review B)

Adsorption of phenylglycine on copper: Density functional calculations - Blankenburg, S.; Schmidt, Wolf Gero (Physical Review B)

Structure, energetics, and vibrational spectra of perylene adsorbed on Si(001): First-principles calculations compared with STM and HREELS - Preuss, M.; Miotto, R.; Bechstedt, F.; Rada, T.; Richardson, N. V.; Schmidt, Wolf Gero (Physical Review B)